Vertical distribution and trophic structure of the macrozooplankton in a shallow temperate estuary (Ria de Aveiro, Portugal) - Morgado, F. M. (2006)
The zooplankton of the lower part of Canal de Mira (Ria de Aveiro) was sampled during one lunar month. The sampling programme consisted of nine 25 hour fixed-cycles, separated weekly. In each cycle, samples were collected every two hours at three depths (surface, mid-water and above the bottom) with a 500 µm mesh net. The overall effect of the tidal phase was analyzed, taking into account the day and depth of the vertical position of the organisms through a 3-way analysis of variance (ANOVA). The zooplankton densities were, in general, higher at the surface during the night and near the bottom during the day, mainly at spring tide. The variation in the number of species followed a similar pattern to that observed for abundance. Significant differences (p<0.01) between diel and tidal phases were observed. Interaction between phase of the day and depth was also significant (p<0.05), with higher organism densities observed during night periods near the bottom. From a trophic point of view the zooplankton community of Canal de Mira was mainly composed of carnivorous and omnivorous species. Carnivores were significantly more abundant around the new and full moon (p<0.001), the omnivores at the new moon (p<0.001) and the herbivores and detritivores at the first quarter of the moon cycles (p<0.001). The density of carnivores was significantly higher at the surface at night and near the bottom during the day (p<0.05). Significant differences in the abundance of omnivores were observed between phases of the day and between depths, with higher values near the bottom during the day. The herbivores and detritivores had significantly higher densities during flood tides (p<0.001).